Conservative treatment of concomitant extraperitoneal bladder rupture and intrabladder blood clot formation: Case report of application of ureteral catheterization - Fu, Chih-Yuan; Shih, Chun-Han; Chang, Po-Yen; Hsiao, Chi-Hao; Wang, Yu-Chun; Chen, Ray-Jade (Canadian Urological Association Journal, 2012)
Most extraperitoneal bladder ruptures can be treated conservatively with catheter drainage only. However, in patients with concomitant intra bladder blood clot formation and extraperitoneal bladder rupture, surgery for blood clot evacuation and bladder repair are usually needed due to occlusion of the urinary catheter. In our patient, we used a ureteral catheter to bypass the clots in the bladder to provide adequate urinary drainage. This procedure serves as a valuable tool in the conservative treatment of extraperitoneal bladder injury.